Oxygen isotope fractionation in the siderite-water system between 8.5 and 62 °C. (1st January 2018) - van Dijk, Joep; Fernandez, Alvaro; Müller, Inigo A.; Lever, Mark; Bernasconi, Stefano M.
Abstract: The oxygen isotope composition of siderites can be used to deduce the temperature and/or oxygen isotope composition of the fluids from which they precipitated. Previous siderite-water oxygen isotope fractionation calibrations are not well constrained at temperatures below 33 °C where most of the siderite forms at the Earth's surface. Moreover, the few experimental low temperature calibration points available are possibly inaccurate as the corresponding siderites may not have formed in equilibrium with the solution. In this study, we synthesized siderite in the laboratory from 8.5 to 62 °C, using both active-degassing experiments and microbial cultures. We used the enzyme carbonic anhydrase, which significantly reduces the equilibration time of oxygen isotopes among all dissolved inorganic carbon (DIC) species and water to minimize siderite formation out of equilibrium. Our calibration is based on many more data points than previous calibrations and significantly reduces the uncertainty in siderite-water oxygen isotope fractionation in natural siderites formed at low temperatures. The best fit equation is 1000 ∗ ln α = 19.67 ± 0.42 10 3 T - 36.27 ± 1.34 where α (1000 + δ 18 Osiderite /1000 + δ 18 Owater ) is the fractionation factor and T is the temperature in Kelvin.